POETICS OF THE IMAGE OF RAIN IN UZBEK POETRY - Haydarova Marjona Shuxrat kizi (International Journal of Literature and Language Studies, 2026)
This article explores the aspects related to the poetics of rain in Uzbek poetry, alongside providing an analysis of poetic lines featuring the image of rain. Furthermore, through a comparative method, the lexical meanings of poetic sentences are comprehensively elucidated by contrasting them with one another. The poems featuring the image of rain in Uzbek poetry possess distinct symbolic characteristics. Below, we analyze step-by-step the poems used in contemporary Uzbek poetry that contain the word